Production and characterization of whey protein concentrate (WPC) based nano-fibers - (:unkn) unknown (Trans Tech Publications Ltd, 2018)
In this study, whey protein concentrate (WPC) and poly (ε-caprolactone) (PCL) composite nanofibers were prepared by electrospinning in the diameter of 50-350nm. Characterization tests of the polymer solutions such as density, viscosity, conductivity was studied. Fourier-transformed infrared spectroscopy (IR) results confirmed that the processed fibers were composed of both PCL and WPC constituents. Morphology of nano-fibers composite was observed using scanning electron microscopy (SEM). Moreover the PCL/WPC nano-fibers with high WPC content exhibited the maximum tensile strength (about 1.40 MPa). © 2018 Trans Tech Publications, Switzerland.
Keywords: Composite nano-fibers; Electrospinning technique; Nanomaterials; Polycaprolactone; Whey protein concentrate